The Theme of “Hearing” in the Holy Quran: A Contextual Semantic Study in Light of Epistemology - Al-Wadaei, Fatima Amer Mohammed (Arts for Linguistic & Literary Studies, 2024)
The research delved into the theme of "hearing" in the Holy Quran, employing thorough study and analysis to elucidate its nuanced meanings across various contexts, guided by epistemological considerations. Structured into three sections, the study initially examines the term "hearing" in isolation, followed by its conjunction with "knowledge," and finally with "sight." Through semantic exploration within an epistemological framework, the research underscores that "hearing," when scrutinized as a cognitive instrument, traverses from sensory perception of sound to conscious engagement facilitating experiential learning. Notably, the study reveals that "hearing" serves as a pivotal conduit to cognitive understanding, particularly when intertwined with other sensory modalities. Furthermore, it highlights that "hearing" predominantly intertwines with "knowledge" in contexts concerning intentions and the depths of the human psyche, in contrast to its association with "sight," which pertains to visual perception, whether in worldly experiences or in deferred envisioning indicating the hereafter.